Partitioning of Forage Mass and Nutritive Value in Sunn Hemp Leaf and Stem Components - Isaac Lepcha; Harley D. Naumann (International Journal of Agronomy)
Sunn hemp (SH; Crotalaria juncea L.) is a fast-growing, annual, warm-season tropical legume that could complement less productive cool-season forages such as tall fescue during summer. Little is known about seasonal forage mass and nutritive value partitioning in SH plant components when SH is managed for forage. We determined partitioning of forage mass and nutritive value (crude protein (CP), in vitro true digestibility (IVTD), neutral detergent fiber (NDF), acid detergent fiber (ADF), and neutral detergent fiber digestibility (NDFD)) concentrations in SH leaves and stems harvested 35, 45, and 55 days after planting (DAP) at Bradford Research Center, Columbia, MO, in a 2-year field study. Leaf and stem mass increased with increasing DAP and was greatest (P≤0.05) at 55 DAP followed by 45 and 35 DAP. Stems contributed most to the total forage mass beyond 45 DAP. Across years, CP was greatest (P≤0.05) in leaves (281 g kg−1 DM) and lowest for stems (81 g kg−1 DM) at 55 DAP. The lowest NDF (P≤0.05) was observed in leaves (251 g kg−1 DM) and stems (585 g kg−1 DM) at 35 DAP. Acid detergent fiber was lowest (P≤0.05) for SH leaves (178 g kg−1 DM) and stems (484 g kg−1 DM) at 35 DAP. Digestibility of leaves was greater than that of stems and generally decreased with maturity. The nutritive value of leaves was consistently greater than that of stems and decreased with maturity, except for CP of leaves, which was maintained throughout the season. Results suggested that SH leaves can maintain forage mass and greater quality than its stem throughout the growing season.